In the Clergy’s Sights: Making Anabaptists Visible in Reformed Zurich - David Y. Neufeld (Religions)
This article examines how Reformed pastors’ understanding and exercise of their office shaped their response to Anabaptists living in rural parishes of the Swiss Confederation in the seventeenth century. In the wake of Swiss reformations, illicit Anabaptist communities continued to represent a threat to territorial religious unity and the Reformed clergy’s spiritual leadership, but the precise contours of their activity and social influence at a village level remained obscure. In the absence of a clear picture of dissent, Reformed churchmen endeavored to make Anabaptism visible, employing tools of information management, into which their training had initiated them. A series of cases from rural jurisdictions (the counties (Landvogteien) of Kyburg and Grüningen) and a seat of ecclesiastical power (Zurich) illustrate how documentary production, organization, and activation consistently drove this project forward. These means rendered Anabaptist life perceptible, facilitating and justifying its elimination by Reformed governments.